Bouchon - Keller, Thomas; Cerciello, Jeffrey (New York : Artisan, 2004)
Presenting the finest in French bistro cookery, the celebrated chef and author of The French Laundry Cookbook introduces nearly 150 recipes that emphasize a variety of emblematic bistro dishes, including soupe l'oignon grantin e, steamed mussels, steak frites, confit of duck, and more.
1. First impressions -- 2. Anytime -- 3. First courses -- 4. Main courses -- 5. Desserts.
Includes index.
Keywords: COOKERY, FRENCH